Levels of salivary IgA in treated and untreated coeliac disease. Issue 9 (September 1972) - Wallington, T.; Ajdukiewicz, A. B.; Read, A. E.; Jones, J. Verrier
Abstract : Estimations of the concentration of secretory IgA have been performed on 152 specimens of saliva from 46 patients with adult coeliac disease. The results are compared with values observed in 20 normal subjects. The mean salivary IgA concentration was 9 mg% in 36 patients on a normal diet and 7·9 mg% in 21 patients on a gluten-free diet. In 20 normals the mean salivary IgA was 7·1 mg%. Nine patients were studied before and after gluten exclusion. Seven of these showed a marked fall in salivary IgA concentration after gluten was excluded.